Cross-Sectional Analysis of IL-6, TNF-α, Adiponectin, Leptin, and Klotho Serum Levels in Relation to BMI Among Overweight and Obese Children Aged 10–14 in La Rioja, Spain - Beatriz Fernández-Vallejo; Francisco Jiménez Monteagudo; Lourdes Romero; Maria Isabel López Aznárez; María del Carmen Romero Cobas; Laura Pérez-Martínez (Children)
Background: Childhood obesity is a major public health concern, being linked to an increased risk of metabolic disorders and cardiovascular disease. Even in childhood, obesity is associated with systemic low-grade inflammation, which is a critical factor in the development of atherosclerosis and a predictor of cardiovascular morbidity and mortality. Objectives: To describe the prevalence of obesity and examine the relationship between IL-6, TNF-α, adiponectin, leptin, the leptin/adiponectin (L/A) ratio, and Klotho levels with BMI in children. Methods: This cross-sectional study included children aged 10–14 years from La Rioja, Spain. Participants were selected based on BMI criteria for overweight (85th–95th percentiles) and obesity (>95th percentile). Socio-demographic and anthropometric data and blood samples were collected and analyzed for IL-6, TNF-α, adiponectin, leptin, and Klotho. Results: A total of 340 participants were included, with 276 (81.2%) classified as normal weight and 64 (18.8%) as overweight or obese. Mean age was similar between groups (p = 0.40). Obesity was more prevalent in males (59.4%, p = 0.048). Obese participants had higher mean birth weight (p = 0.003), current height (p = 0.04), BMI (p < 0.0001), and abdominal circumference (p < 0.0001). BMI correlated positively with leptin (r = 0.54, p = 0.0008) and the L/A ratio (r = 0.40, p = 0.025), showing sex-specific differences. Conclusions: This study underscores leptin and the L/A ratio as potential biomarkers of metabolic dysregulation in childhood obesity, particularly in females. Longitudinal studies are needed to confirm these findings and assess the clinical utility of these biomarkers in pediatric obesity management.